Modulation, coding, and synchronization for mobile and very small satellite terminals, as part of the updated DVB-S2 standard - Lee, Lin-Nan; Eroz, Mustafa; Becker, Neal (International journal of satellite communications and networking, 2016)
Summary After 10 years of successful deployment, the second‐generation satellite standard for digital video broadcasting, DVB‐S2, has recently been updated. Very low signal‐to‐noise ratio modes to better support mobile and very small terminal applications are part of the new standard without changing its fundamental structure. This paper provides a high‐level discussion on several of the most important aspects pertaining to the new very low signal‐to‐noise ratio modulation and coding modes of the updated standard. Copyright © 2015 John Wiley & Sons, Ltd. This paper shows an efficient method of integrating new modulation/coding pairs (MODCOD) that operate at very low signal‐to‐noise ratios (VL‐SNR) into the second‐generation satellite standard for digital video broadcasting standard without changing the fundamental structure of the standard. In particular, the stringent synchronization requirements of the new VL‐SNR MODCODs are met at −10 dB Es/No without penalizing the existing second‐generation satellite standard for digital video broadcasting MODCODs that may co‐exist on the same carrier. Simulation results confirm that the performance of the new VL‐SNR MODCODs is about 1 dB away from the Shannon limit.